Effects of neuroplasticity in people with knee osteoarthritis: A systematic review of the literature. Issue 3 (21st January 2022) - Iuamoto, Leandro Ryuchi; Ito, Fábio Luis Kenji; Tomé, Thales Augusto; Hsing, Wu Tu; Meyer, Alberto; Imamura, Marta; Battistella, Linamara Rizzo
Abstract: Background: Knee osteoarthritis (OA) is associated with chronic inflammation in somatic structures, which alters sensory afferents and leads to plastic changes in the nervous system. Methods: A systematic literature review was carried out, without language restrictions, period, or status of publication. The database used were Medline, EMBASE, Cochrane Library and clinicaltrials.gov. Extra bibliographic references were extracted through the discussion with specialists, and through scientific researches in conference papers. Results: The electronic search found 938 articles. When excluding duplicates and applying the inclusion/exclusion criteria, 5 studies were considered: 2 using EEG and 3 using TMS. Significant reduction of EEG activity in the cingulate medium cortex, reduction of conditioned pain modulation (CPM) in studies with EEG, as well as the occurrence of an association between pain and motor response threshold/intracortical pain facilitation in studies with TMS were observed. Conclusions: The study contributes to a better understanding of the neurophysiological changes seen in the cingulate medium cortex, decrease in CPM and motor response threshold/intracortical pain facilitation. Advances in neuroplasticity studies may aid in the screening for early diagnosis of knee OA in the future. However, more studies are necessary.